2019
DOI: 10.1332/030557318x15167881150799
|View full text |Cite
|
Sign up to set email alerts
|

The impact of management consultants on public service efficiency

Abstract: Public sector organisations often make use of management consultants in policy implementation, but we know little about the outcomes. The paper reports one of the first quantitative evaluations of the impact of consulting advice on efficiency of public sector organisations. We employ an extensive dataset covering English NHS acute care hospital trusts over a four-year period. Based on PCSEs estimations, the findings show a significantly positive relationship between consulting expenditure and organisational in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 34 publications
2
41
0
1
Order By: Relevance
“…This has led scholars to call for more studies on how and why public organizations hire consultants (Ylönen & Kuusela, ). In line with this call, we find that despite observed variations (Perl & White, ), the antecedents of individual public sector organizations' use of MCS, has only been explored to a very limited extent (Biskup & Lindbäck, ; Kirkpatrick et al, ; Steiner et al, ). Because of the intertwined nature of the use of MCS and reform‐ and change programs, which are typically initiated by management, we turn to upper echelon theory.…”
Section: Antecedents To Management Consulting In the Public Sectorsupporting
confidence: 66%
See 1 more Smart Citation
“…This has led scholars to call for more studies on how and why public organizations hire consultants (Ylönen & Kuusela, ). In line with this call, we find that despite observed variations (Perl & White, ), the antecedents of individual public sector organizations' use of MCS, has only been explored to a very limited extent (Biskup & Lindbäck, ; Kirkpatrick et al, ; Steiner et al, ). Because of the intertwined nature of the use of MCS and reform‐ and change programs, which are typically initiated by management, we turn to upper echelon theory.…”
Section: Antecedents To Management Consulting In the Public Sectorsupporting
confidence: 66%
“…The findings also have practical implications. First, they confirm that MCS form a regular part of the operations in today's public organizations (Kirkpatrick et al, 2018;Saint-Martin, 2012;Steiner et al, 2018) and indicate that change in top management induces a temporary increase in the use of MCS. When planning management succession, GAs might therefore also consider the potential effects the change of CE might have on the use of MCS.…”
Section: Implications For Practicementioning
confidence: 70%
“…These figures need to be interpreted with caution, as they do not capture additional individual service expenditure and are extracted amid variable financial reporting, definitions and approaches. There are also no data that we could source on: the comparison of external versus internal or partnership consultancies from State and Federal governments in Australia; how many external consultancies reports are not made publicly available; or the uptake of the findings from external or internal consultancies. This all arguably contributes to a lack of transparency and ambiguity at the health service, and State and Federal Government levels.…”
Section: External Management Consultancies In Healthmentioning
confidence: 99%
“…EMC expenditure has grown in tandem with rising demand, yet many have been critical of these trends. 2 As a study conducted by the Royal College of Nursing in the UK, 12(p6) based on freedom of information (the only study of its kind), concluded: 'questions need to be asked … about whether external consultancy offers value for money'. This is especially valid in the UK and Australia publicly funded services where public accountability is vital.…”
Section: External Management Consultancies In Healthmentioning
confidence: 99%
See 1 more Smart Citation